Perspectives on conducting "sex-normalising" intersex surgeries conducted in infancy: A systematic review. - Luke Muschialli; Connor Luke Allen; Evelyn Boy-Mena; Aiysha Malik; Christina Pallitto; Åsa Nihlén; Lianne Gonsalves (Public Library of Science (PLoS), 2024)
Children with intersex variations continue to be subject to elective, irreversible, "sex-normalising" surgical interventions, despite multiple human rights and legislative bodies calling for their prohibition. Our systematic review aims to understand how medical literature reports rationales for "sex-normalising" surgical interventions conducted in childhood, and how they are contextualised within the medical and social controversy surrounding such interventions. PubMed, EMBASE and CINAHL were searched for English language, peer-reviewed articles reporting primary data on elective, genital, "sex-normalising" surgical interventions conducted on individuals <10 years, published 01/07/2006-30/06/2023 (PROSPERO ID: CRD42023460871). Data on outcomes reported, rationale for the conduct and timing of interventions and acknowledgement of controversy were extracted. Narrative synthesis described rationales and controversy. Risk of bias was assessed using Johanna Briggs Institute Tools. 11,042 records were retrieved, with 71 articles included for analysis. One of the most common outcomes collected in included literature were cosmetic outcomes, primarily reported by surgeons or parents. 62.0% of studies reported no rationale for intervention timing, 39.4% reported no rationale for conduct and 52.1% acknowledged no controversy in intervention conduct. Rationales included parental desire for intervention, anatomical/functional/cosmetic reasons, and a perceived goal of aligning with sex assigned by surgical teams or parents. Controversies addressed included concerns about the quality of interventions, the ethics of intervention conduct and gendered and social considerations. "Sex-normalising" interventions are conducted based largely on rationales that were not adequately supported by evidence, a desire from parents and surgeons to match genital cosmesis typically ascribed to male and female bodies, and a parental desire for intervention conduct. Legislating and medical regulatory bodies should advocate for ending the conduct of irreversible, elective, "sex-normalising" interventions conducted without the full, free and informed consent of the person concerned, to promote and protect the highest attainable standard of health for people with intersex variations.